Treatment Patterns and Outcomes of Elderly Patients With Potentially Curable Esophageal Cancer - Yang, Yang; Chen, Mengyuan; Xie, Jiping; Ji, Yongling; Sheng, Liming; Qiu, Guoqin; Du, Xianghui; Wei, Qichun (Frontiers in Oncology, 2022)
Objectives: The proportion of elderly patients with esophageal cancer (EC) is increasing due to prolonged life expectancy and aging process. The aim of the study is to explore the optimal treatment strategy for elderly patients (aged ≥70 years) with locally advanced EC. Methods: Eligible patients with cT2-4aNxM0 EC were identified in the Surveillance, Epidemiology, and End Results database from 2010 to 2016. Treatment patterns were divided into five groups: surgical resection (S), chemoradiotherapy (CRT), trimodality therapy (CRT+S), radiotherapy (RT), chemotherapy (CT), or observation with no treatment (Obs). Survival between groups was compared using the log-rank test, and the Cox proportional hazards model was used to identify factors associated with overall survival (OS). Results: A total of 2917 patients with potentially curable EC were identified. Of all the patients included, 6.7%, 51.8%, 18.0%, 9.4% and 3.6%received S, CRT, CRT+S, RT, and CT, respectively, whereas 10.6% underwent Obs. The 3-year OS estimates were 30.2% (95% confidence interval [CI]: 23.5–38.9%), 25.4% (95% CI: 22.8–28.3%),44.3% (95% CI: 39.3–49.9%), 11.4% (95% CI: 7.7–17.0%), 16.1% (95% CI: 9.1–28.3%), and 5.6% (95% CI: 3.2–9.8%) for S, CRT, CRT+S RT, CT, and Obs (p<0.001), respectively. Overall, patents underwent CRT+S had the longest OS, compared to other treatment patterns, and the survival difference was not significant between patients receiving CRT and S(p=0.12) in the elderly population. However, the survival benefits of trimodality therapy over CRT gradually weakened with the increase in age, and became statistically non-significant for EC patients aged ≥80 years (p=0.35). Multivariate analysis showed that treatment patterns, age, sex, tumor grade, T stage, N stage, and marital status were significantly associated with OS. Conclusion: Generally, the use of trimodality therapy was associated with the longest OS, the survival benefits were comparable between CRT and S alone, and CRT was superior to RT or CT alone in elderly patients with curable EC. For patients intolerable to surgery or aged ≥80 years, definitive CRT should be considered as a preferable option.